First record of Helicoverpa armigera (Lepidoptera: Noctuidae) feeding on Plectranthus neochilus (Lamiales: Lamiaceae) in Brazil - Krinski, Diones; Godoy, Ana Flavia [UNESP] (Florida Entomological Soc, 2015)
Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) is a polyphagous agricultural pest recorded in Europe, Asia, Africa, Oceania, and recently South America. Larvae of H. armigera are recorded from over 67 host families, including Asteraceae, Fabaceae, Malvaceae, Poaceae, and Solanaceae. This study documents for the first time H. armigera larvae feeding on inflorescences of boldo-rasteiro Plectranthus neochilus Schltr. (Lamiales: Lamiaceae). The species was identified according to external and internal characteristics of adults, morphology of eggs, and by molecular characterization.
Keywords: identification; morphology; molecular characterization; new host record; boldo-rasteiro